PEMBAGIAN KERJA DALAM RANGKA MENINGKATKAN EFEKTIVITAS KERJA KARYAWAN - Amrita, Divya; Sutaryadi, Sutaryadi; Ninghardjanti, Padni (Pendidikan Administrasi Perkantoran FKIP Univesitas Sebelas Maret, 2012)
Abstract: The objective of research is to find out the implementation of labor division in improving the effectiveness of employee performance in Human Resource Division of PT. Pos Indonesia Surakarta in 2010/2011. This research employed a qualitative approach, descriptive method, and single embedded research strategy. The sampling techniques used were purposive sampling and snowball sampling. Techniques of collecting data used were interview, observation, and documentation. The data validation was done using data and method triangulation. Technique of analyzing data used was an interactive model of analysis one. Considering the result of research, it can be concluded The implementation of labor division in Human Resource Division of PT. Pos Indonesia Surakarta in 2010/2011 includes a labor division implementation time. The labor division is carried out when the work exists, both routine and incidental works. Keywords: implementation of labor division, effectiveness of employee performance